The effect of different quantity of filtering materials to the performance of biofilter system for wastewater treatment - Mohd Aiman, Mohd Ali (2010)
Nowadays, clean water resources are reduced due to water pollution problems. Pollution carried by the wastewater is considered as one of the contributors to the water pollution problems. One of the ways to reduce water pollution is to treat wastewater at the source points. This can be accomplished by constructing a biofilter system at the point sources of polluted water before being discharged into rivers. Biofilter system consists of several compartments of filtration media, which is located at Kolej Kediaman 3, UMP Gambang. This research focused on the performance of biofilter for water quality improvement before and after passing through the filtration system and the effect of increasing the quantity of filtration materials. This system utilizes sponge, sand and granite, EM rnudball, activated carbon, charcoal and empty palm oil fruit bunch as its filtration media for the removal of constituents in water. Results of these experiments were analyzed by evaluating the water quality parameters such as Turbidity, SS, AN, BOD and COD in comparison to Standard A and Standard B Environmental Quality Standards Act (1974) and in terms of their percentages of removal. The results indicated that all effluent discharge of parameters pH, temperature, COD, BOD, and TSS are complying Standard B only. However, the performance of biofilter in terms of BOD, COD, and TSS removal is excellent where the removal efficiency range from 0.97% to 4.90 1/o, 2.63% to 51.63% and 17.05% to 67.31% respectively. The study also found out that the concentration of pollutants after the treatment is decrease as the quantity of filtering materials increased and the percentages of removal increase as the quantity of filtering materials increased.